Terminologia kinematograficzna w rosyjskich i polskich słownikach jednojęzycznych (analiza semantyczna) - Borys, Iwona (Acta Polono-Ruthenica, 2018)
The vocabulary of the cinema (hereinafter referred to as Cinematic terminology) represents one of the most important components of 20th and 21th century accessions to the Russian and Polish language. This research is aimed to identify and compare the meaning of words used in cinematic terminology. In this research, the researcher applies descriptive qualitative method. The results shows eighteen types of movie making terms. Another conclusion is that most of the cinematic terms are borrowed from English, and that the borrowed terms are the same in both languages. With the present work, we hope to make a contribution to the comparative studies of the cinematic terminology by improving the record for some movie words what are included in the most populares Russian and Polish monolingual dictionaries.